The Development of Model Family-Centered Empowerment on Caring for Children with Leukemia - Yuni Sufyanti Arief; Nursalam Nursalam; I Dewa Gede Ugrasena; Shrimarti Rukmini Devy; Eileen Savage (Universitas Airlangga, 2018)
Introduction: Children with leukemia desperately need serious attention, commitment and it is a hard struggle for family members. Powerlessness experienced by the family will affect the ability of the families to provide care for their children. Many factors can affect the empowerment of families in providing care to their families.Methods: The purpose of this study was to develop a family-centered empowerment model related to the family's ability to care for their child suffering from leukemia. The research design used was an explanation survey. The sample consisted of 140 families with children suffering from leukemia in the pediatric ward of Dr. Soetomo Hospital.Results: The family-centered empowerment model was formed from the family factor, patient factor and nurse factor. The greatest effect was on the nurse factor, with the T statistic value = 6.590.Conclusion: Family factors and nurse factors need to be taken into account in family-centered empowerment. The patient factor has little influence on family empowerment in relation to caring for children. More research is needed on family-centered empowerment models in relation to their ability to care for children with leukemia. For example, a nurse providing a nursing intervention, especially a pediatric nurse, in relation to empowering a parent at the time of caring for their child with leukemia.